2004
DOI: 10.1074/jbc.m310679200
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Low Density Lipoprotein Receptor-related Protein 1 to Caveolae in 3T3-L1 Adipocytes in Response to Insulin Treatment

Abstract: The insulin-induced translocation of low density lipoprotein receptor-related protein 1 (LRP1) from intracellular membranes to the cell surface in 3T3-L1 adipocytes was differentiation-dependent and did not occur in 3T3-L1 fibroblasts. Prompted by findings that the plasma membrane of 3T3-L1 adipocytes was rich in caveolae, we determined whether LRP1 became caveolae-associated upon insulin stimulation. The caveolae domain was isolated by the well characterized detergent solubilization and sucrose density ultrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 79 publications
2
36
0
Order By: Relevance
“…Our results reveal that pro-cath-D colocalized with LRP1 at the cell surface in lipid rafts. At the cell surface, LRP1 has been shown to be localized in clathrin-coated pits and in lipid rafts (Boucher et al, 2002;Wu and Gonias, 2005;Zhang et al, 2004). Here, we show that LRP1 overexpression directs pro-cath-D to the lipid rafts.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our results reveal that pro-cath-D colocalized with LRP1 at the cell surface in lipid rafts. At the cell surface, LRP1 has been shown to be localized in clathrin-coated pits and in lipid rafts (Boucher et al, 2002;Wu and Gonias, 2005;Zhang et al, 2004). Here, we show that LRP1 overexpression directs pro-cath-D to the lipid rafts.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, some of the cell surface LRP1 is located in lipid rafts (Wu and Gonias, 2005;Zhang et al, 2004). Therefore, we next investigated whether pro-cath-D and LRP1 might colocalize at the cell surface in these micro-domains.…”
Section: Overexpressed Lrp1 Directs Pro-cath-d To Lipid Rafts In Tramentioning
confidence: 99%
“…The low density lipoprotein receptor-related proteins (LRPs) are another important protein family involved in formation of lipid rafts (45). Besides LRP-1, we also detected LRP-6, which was not known to be involved in insulin signaling.…”
Section: Discussionmentioning
confidence: 68%
“…There was also a decrease in pro-cath-D endocytosis in LRP1-silenced fibroblasts ( Figure 1A, panel d) when uptake was measured over 18 h ( Figure 1A, panel c, compare lanes 3 and 4, and panel e for quantification). We then investigated pro-cath-D internalization by LRP1 using MEF that lacked M6P receptors ( Figure 1B Pro-cath-D and ectopic cath-D do not modulate LRP1b-chain tyrosine phosphorylation in fibroblasts The LRP1 at the plasma membrane is located in clathrin-coated pits and lipid rafts (Boucher et al, 2002;Zhang et al, 2004;Wu and Gonias, 2005), and it has been suggested that there are LRP1-induced signal transduction pathways triggered by tyrosine phosphorylation or RIP in lipid rafts (Boucher et al, 2002; von Cathepsin D, endocytosis and LRP1 RIP D Derocq et al Arnim et al, 2005;Wu and Gonias, 2005). We observed that LRP1b overproduction directs pro-cath-D to the lipid rafts (Beaujouin et al, 2010), suggesting that cath-D modulates the tyrosine phosphorylation of LRP1, as shown for the PDGF-BB (Boucher et al, 2002;Loukinova et al, 2002;Boucher and Gotthardt, 2004;Newton et al, 2005) and CTGF (Yang et al, 2004) growth factors, the tPA serine protease (Hu et al, 2006) and in fibroblasts transformed with v-Src (Barnes et al, 2001(Barnes et al, , 2003.…”
Section: Resultsmentioning
confidence: 99%